Health effects of the #metoo movement by gender: Public health implications of a social movement. (September 2021) - Huseth-Zosel, Andrea L.; Larson, Mary; Nelson, Kjersten
Abstract: The objectives of the present study are to assess health impacts of the #metoo campaign by gender and assess health impacts of different levels of sexual harassment exposure. Faculty, staff and students at a mid-sized university in the United States were invited to participate in an online survey focused on experiences with and perceptions of #metoo. Differences were found by gender for the number of days experiencing physical and emotional health benefits/concerns. Sexual harassment exposure levels impacted health outcomes as well. The present data highlight gender disparities related to physical and mental health concerns that have emerged since #metoo.